Creep/creep-recovery response of fibredux 920C-TS-5-42 composite under flexural loading - Rui Miranda Guedes (1999)
The flexural behavior of unidirectional composites at 90 degrees to the axis was investigated. The experimental data and finite element method results indicate that beam specimens undergo large deformations. An analytical model was developed to calculate the correct maximum stress level obtained during the flexural tests. Models have been developed to describe the time-dependent viscoelastic-viscoplastic stress-strain relationship of unidirectional fibre reinforced thermoset matrix composites. A procedure that extends the classical lamination theory to include time related response of composite materials for membrane and flexural loading resulted in a FORTRAN program, LAMFLU, For Fibredux 920C-TS-5-42 graphite-epoxy composite the constants in the stress-strain relationships were determined from data obtained in four-point bending tests. The model characteristics for tensile loading have been determined by Qin [1] and were adapted to the LAMFLU procedure. The maximum strain history calculated with both models was compared with experimental results from two different flexural loadings programs.